Alienation and Imagination. Charlie Kaufman’s “Synecdoche, New York” - Sabolius, Kristupas (Religija ir kultūra, 2012)
This article examines the link between time, imagination, and synthesis in Charlie Kaufman’s “Synecdoche, New York”. Unable to find the unity among separate fragments of life and “to join the beginning to the end“, the protagonist Caden Cotard starts mounting a new play – “an artistic piece of brutal realism and honesty“. However, this attempt could be interpreted as a deliverance of the power of imagination – the Kantian Einbildungskraft, which permits the unification of sensibility and understanding as well as provides us with the radical experience of the Otherness. The chronological flow of events is decomposed and recomposed during the rehearsals of Caden’s performance, as well as in the editing sequence of the film itself, resuscitating, through the perplexity and confusion, the vitality of consciousness vis-à-vis its own mortality. Thus, the article shows that the awareness of one’s death provides with deeper insights into reality, while abandoned identities correspond to a temporal opening of and for the Other.
Keywords: synecdoche; imagination; time; synthesis; Otherness